PERBANDINGAN APLIKASI EKSTRAK SEREH DAPUR DAN ESTRAK SEREH WANGI TERHADAP RADANG MUKOSA MULUT (Penelitian Laboratorik pada Tikus Wistar Strain LMR) - Mindya Juniastuti; Tjut Fatluna (Faculty of Dentistry, Universitas Indonesia, 2015)
Inflammation is one of the body's defence mechanism against irritants, infectious agents, and injury. During its process, pain, swelling, redness, and other discomforts also occur as cardinal signs of inflammation. Therefore, people seek for medicine to encounter those effects. Sereh is one of the herb plants which have anti inflammatory effect. However, effect of Sereh on inglamed oral mucosa has not been clinically examined. The aim of this research is to examine and to compare the influence of Sered Dapur (Cymbopogon citratus) and Sereh Wangi (Cymbopogon winterianus lowitt) extract on inflamed oral mucous induced by Hydrogen Peroxide 10%. Thirteen Wistar rats were used in this research and divided four groups, control group I (3 rats), control group II (3 rats), Sereh Dapur extract groups (4 rats) and Sereh Wangi extract groups (3 rats). All rats in Sereh Dapur, Sereh Wangi and control II groups received 3x10 minutes application of Hydrogen Peroxide 10% on their vestibulum for 3 days, while rats in control gorup I received application of Aquadest. On the 4th day, all groups that received Hydrogen Peroxide 10% were application 3x5 minutes for 3 days for each substance. After rats have been killed their oral mucosa were processed and examine under microscope. Statistical result shows there are differences on oral mucous reaction between Sereh Dapur and Sereh Wangi extract with control group. Based on the research result, it can be concluded that both Sereh Dapur and Sereh Wangi can reduce oral mucous inlammation and Sereh Dapur is more effective than Sereh Wangi in reducing the oral mucous inflammation induced by Hydrogen Peroxide 10%.